2019
DOI: 10.1002/hpja.269
|View full text |Cite
|
Sign up to set email alerts
|

The injury workforce in Western Australia: Findings from a cross‐sectional survey

Abstract: Issue addressed: Since 1986, injury prevention and control has been classified as a National Health Priority. However, no reviews into the injury prevention workforce have been conducted in Australia since 2011 and to date; none has focused specifically on the injury prevention and safety promotion sector in Western Australia (WA). This research sought to review the scope of the injury prevention and safety promotion workforce in WA to gain a greater understanding of sector characteristics, work and needs. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…To our knowledge, this is the first study to understand the characteristics of the child injury prevention workforce in New Zealand and the organisations involved. The findings are consistent with a study by Jancey et al that sought to establish the characteristics of the Western Australian injury prevention and safety promotion workforce 9 . Similar to the present study, they found more than three‐quarters of respondents were female.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…To our knowledge, this is the first study to understand the characteristics of the child injury prevention workforce in New Zealand and the organisations involved. The findings are consistent with a study by Jancey et al that sought to establish the characteristics of the Western Australian injury prevention and safety promotion workforce 9 . Similar to the present study, they found more than three‐quarters of respondents were female.…”
Section: Discussionsupporting
confidence: 93%
“…The questionnaire consisted of 35 questions (see Supplementary Information) and took approximately 15 minutes to complete. Where possible, items were derived or adapted from existing research 9,11-13 . The survey was piloted with three people from the injury prevention field and modified where required.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations